2010
DOI: 10.1093/jmedent/47.3.376
|View full text |Cite
|
Sign up to set email alerts
|

The Salivary Gland Transcriptome of the Eastern Tree Hole Mosquito,Ochlerotatus triseriatus

Abstract: Saliva of blood-sucking arthropods contains a complex mixture of peptides that affect their host's hemostasis, inflammation, and immunity. These activities can also modify the site of pathogen delivery and increase disease transmission. Saliva also induces hosts to mount an antisaliva immune response that can lead to skin allergies or even anaphylaxis. Accordingly, knowledge of the salivary repertoire, or sialome, of a mosquito is useful to provide a knowledge platform to mine for novel pharmacological activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Based on our proteomic analyses (Figs. 3B and 6) as well as transcriptomic analyses by others (16,38), SGSs are the only anopheline or culicine saliva proteins whose mass approximates the value predicted for this ϳ387-kDa protein. In support of our hypothesis that Sgs4 and Sgs5 are immunomodulatory, it has recently been shown that bacterial RHS/YD-repeat proteins (distant relatives of SGS) play a role during the deactivation of human macrophages by the bacterial pathogen Burkholderia pseudomallei (39).…”
Section: Discussionmentioning
confidence: 74%
“…Based on our proteomic analyses (Figs. 3B and 6) as well as transcriptomic analyses by others (16,38), SGSs are the only anopheline or culicine saliva proteins whose mass approximates the value predicted for this ϳ387-kDa protein. In support of our hypothesis that Sgs4 and Sgs5 are immunomodulatory, it has recently been shown that bacterial RHS/YD-repeat proteins (distant relatives of SGS) play a role during the deactivation of human macrophages by the bacterial pathogen Burkholderia pseudomallei (39).…”
Section: Discussionmentioning
confidence: 74%
“…Proteins containing single or multiple Kunitz domains were described and functionally characterized in ticks, such as Ixolaris, a double-Kunitz protein, and Pentalaris, containing five domains [57], [58], [59], [60], [61], both acting as blood-clotting inhibitors of the extrinsic pathway. The Kunitz fold can also perform functions beyond protease inhibition, such as ion channel inhibition [62], [63], [64], [65]; in R. appendiculatus , a modified Kunitz domain peptide [66] was shown to activate maxiK channels in an in vitro system, suggesting a vasodilator function.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the hypersensitivity responses of humans to mosquitoes and sand flies is not surprising. Salivary components from sand flies and mosquitoes are considerably different sharing only a small number of molecules with significantly divergent sequences (Anderson, Oliveira et al 2006; Calvo, Sanchez-Vargas et al 2010). In fact, several sand fly salivary proteins are unique to these insects (Anderson, Oliveira et al 2006), potentially accounting for the distinct hypersensitivity responses observed here.…”
Section: Discussionmentioning
confidence: 99%